Aryl acrylonitriles synthesis enabled by palladium-catalyzed α-alkenylation of arylacetonitriles with vinyl halides/triflates - Jiang, Yonggang; Wang, Bijun; Liu, Dongxiang; Xia, Dazhen; Liu, Zhengfen; Li, Liang; Deng, Guogang; Yang, Xiaodong (Frontiers in Chemistry, 2022)
Aryl acrylonitriles are an important subclass of acrylonitriles in the medicinal chemistry and pharmaceutical industry. Herein, an efficient synthesis of aryl acrylonitrile derivatives using a Palladium/NIXANTPHOS-based catalyst system was developed. This approach furnishes a variety of substituted and functionalized aryl acrylonitriles (up to 95% yield). The scalability of the transformation and the synthetic versatility of aryl acrylonitrile were demonstrated.